Does Militancy Affect Female Students? A Cross Sectional Based Study of District Bajaur Khyber Pakhtunkhwa - Hammad Zada; Saima Sarir; Nasar Shah; Asma Bibi (Journal of Peace, Development and Communication, 2022)
A cross-sectional study was carried out with the sole purpose of assessing the effects of militancy on female students in District Bajaur. Using Sekaran criterion, a sample size of 169 respondents was purposefully chosen. A conceptual framework consisting of a dependent variable (the nature of drop out) and an independent variable (Militancy). For primary data collection, a well-structured questionnaire was used. Furthermore, descriptive (frequency and percentage distribution) and inferential statistics were used to analyses the data (chi-square test). Thus, the study revealed a highly significant association (P=0.000) between the nature of drop out and militancy indictors (statements), namely, terrorists had destroyed schools in the study area, schools were closed due to security issues, militancy is a formidable barrier to female education, militants have threatened girl schools, local residents were displaced due to militancy, and academic session of children suffered due to militancy. As a result, the government should implement legislative and budgetary measures to reduce dropout rates, such as providing financial assistance, a safe environment, school infrastructure, basic educational facilities in schools, and employment prospects, particularly for female students. Some of the recommendations have been forwarded in light of the current investigation.